Information and communication technology adoption among small and medium enterprises in the northern region of Malaysia - Mathivannan, Jaganathan (2019)
Malaysian small and medium enterprises (SMEs) still have not fully utilized the information and communications technology (ICT) tools to their fullest potential. Hence, there is a need to determine the factors that contribute to ICT adoption among SMEs. This study was undertaken to examine the variables that contribute to the ICT adoption among the SMEs in Malaysia by examining the relationships between relative advantage, security, compatibility, complexity, cost and environmental pressure (normative, mimetic and coercive) and JCT adoption. Additionally, government support was examined as a moderator. The triangulation theory approach, which integrates technology-organization environment, diffusion of innovation and the institutional theory was used to explain the relationships between the variables. A total of 183 owners-managers of SMEs, representing a response rate of 47.6 percent, participated in this study. The data was collected via self administered questionnaires, and PLS-SEM was used to analyze them and test the hypotheses. Statistical results indicated that relative advantage and security are positively related while complexity is negatively related to ICT adoption. Conversely, compatibility, cost and environmental pressure (normative, mimetic and coercive) are not related to ICT adoption. Moreover, the moderating test result reveals that government support only moderates the relationship between security, compatibility, complexity and cost, and ICT adoption. Conversely, no empirical support is found for the moderating effect of government support on the relationship between relative advantage and environmental pressure, and ICT adoption. The major theoretical contribution of this research is that it examines environmental pressure as a multidimensional independent variable. Besides that, the study also examines the role of government support as a moderating variable. This study also provides some suggestions to SMEs, policy-makers, ICT support system developers and vendors on ways to improve existing plan and policies for encouraging ICT adoption among SMEs. Finally, recommendations for future research are discussed.